Strategi Movie Learning Dalam Pembelajaran Akidah Akhlak - Siti Fatimah; Muhammad Zulkifli (Darussalam, 2021)
Abstract: Inappropriate strategy implementation in learning activities will have an impact on lowmotivation and enthusiasm for student learning during the learning process. To overcome theseproblems, it is necessary to choose the right strategy. In this article, the focus is on discussingmovie learning strategies to overcome problems of interest in learning. Sources of data in thisstudy used books and scientific journals related to learning strategies. In this study using thelibrary research method to obtain information about the nature of learning strategies and theeffectiveness of movie learning strategies that can arouse students' interest in learning the subjectof moral ethics.Keywords: Movie Learning Strategy, Aqidah Akhlak,Abstrak: Penerapan strategi yang kurang tepat pada kegiatan belajar akan berdampak padarendahnya motivasi dan semangat belajar siswa saat proses pembelajaran itu berlangsung. Untukmengatasi permasalahan tersebut, maka perlu pemilihan strategi yang tepat. Dalam artikel inifokus membahas strategi pembelajaran movie learning untuk mengatasi permasalahan minatbelajar. Sumber data dalam penelitian ini menggunakan buku-buku dan jurnal ilmiah yangberkaitan dengan strategi pembelajaran. Dalam penelitian ini menggunakan metodelibraryresearch untuk memperoleh informasi tentang hakikat strategi pembelajaran dan efektivitasstrategi movie learning yang dapat membangkitkan minat belajar siswa terhadap mata pelajaranakidah akhlak.Kata Kunci: Strategi Movie Learning, Akidah Akhlak